2014
DOI: 10.1007/s00464-014-3665-9
|View full text |Cite
|
Sign up to set email alerts
|

Technical difficulty according to location, and risk factors for perforation, in endoscopic submucosal dissection of colorectal tumors

Abstract: ESD was slower for sigmoid colon tumors than for tumors in other areas, suggesting that ESD was technically more difficult in the sigmoid colon than in other colorectal areas. Submucosal fibrosis was independently associated with perforation during colorectal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 23 publications
4
73
1
3
Order By: Relevance
“…In our study, we looked at large tumors (>10 cm 2 ) and found that tumor size was technically demanding for perforation, which is consistent with what was observed in previous studies (14)(15)(16). However, a recent study found that when ESD were performed before 2010, tumor size might be technically demanding for perforation, but when ESD was performed after 2010 in the same institution, the results were different (11). Our data were collected from the beginning of performing CR-ESD; therefore, a performance learning curve must be considered.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, we looked at large tumors (>10 cm 2 ) and found that tumor size was technically demanding for perforation, which is consistent with what was observed in previous studies (14)(15)(16). However, a recent study found that when ESD were performed before 2010, tumor size might be technically demanding for perforation, but when ESD was performed after 2010 in the same institution, the results were different (11). Our data were collected from the beginning of performing CR-ESD; therefore, a performance learning curve must be considered.…”
Section: Discussionsupporting
confidence: 87%
“…Mizushima et al (11) reported technically difficult ESD based on location, and their analysis suggested that sigmoid colon was more technical demanding for CR-ESD. However, there have been no reports that describe risk factors for technical difficulty of large-sized CR-ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate EMR with uncertain resected locations might deteriorate patients’ quality of life. When it comes to the lesion over 20 mm performed en bloc resection by ESD, the location of the resected site is clear [17-21]. …”
Section: Discussionmentioning
confidence: 99%
“…This technical difficulty is likely to be associated with complications, especially perforation. Previous studies used long procedure times (more than 120 or 150 min); perforation and piecemeal resection mark the technical difficulty of colorectal ESD, and it was found that technical difficulty was associated with factors including mobility of tumor location (mobile: sigmoid or transverse colon; fixed: rectum, descending colon, ascending colon, or cecum), lesions at a fold or flexure, huge tumor (≥5 or ≥4 cm), tumors associated with scarring or local recurrence (presence of severe fibrosis) [31,32,33]. In recent years, in order to obtain adequate tissue tension and clear visibility of the tissue, reduce operating time and improve security, many ESD-assisted methods have been developed, such as the clip-with-line method, the sinker-assisted method, the internal traction method, the outer route method, the double-scope method, the external forceps method and the endoscopic surgical platform [34].…”
Section: Technical Aspects Of Endoscopic Approaches For Early Crcmentioning
confidence: 99%